Farmers' perceptions of agricultural land use changes in Nepal and their major drivers. (1st April 2019) - Paudel, Basanta; Zhang, Yili; Yan, Jianzhong; Rai, Raju; Li, Lanhui
Abstract: Historical trends show that the total area of agricultural land in Nepal has changed markedly over time, but few studies have addressed the causative drivers underlying this change. Evaluating the perceptions of farmers is an effective tool for addressing this issue because it reflects the full range of drivers associated with changes in land use. This study utilizes historical agricultural area, population, and climate data for 1910–2010, combined with a series of applied household surveys and focus group discussions to assess farmers' perceptions of these changes and identify the major drivers. The paired t -test was employed to measure differences between various groups of drivers. The total area of agricultural land in Nepal has expanded rapidly since 1910, more intensively in the southern (Tarai) and central (Hill) ecological regions of the country, and has decreased slightly near large cities in recent decades. Farmers' perceptions show that socioeconomic variables were considered to be the crucial drivers of changes in agricultural land use. The three other major drivers were grouped as: neighborhood, climate–topography, and policy drivers. In particular, farmers pointed to the high level of population growth (93.96%) as the main factor underlying the changes, and the majority of drivers are associated with this variable. Access to roads (77.36%), urbanization (33.77%), government policies (23.58%), and remittance impact (16.79%) are other notable triggering variables. The paired t -test results equating variables from different groups of drivers and ecological regions indicate varied significance ( p -values range from 0.004 to 0.983). Our analysis confirms that the synergy between social and natural observations can be integrated to obtain research findings that identify scientific and social issues. The interplay between the drivers should be emphasized in developing plans for sustainable agricultural land use management. Highlights: Evaluated drivers of agricultural land use change in Nepal using farmers' perception. Farmers perceived that socioeconomic factors are the crucial driver. High population growth is the primary factor underlying these changes. Government policies are a salient indicator of agricultural land use change.